PENGARUH LATIHAN PUSH UP DAN CLAP PUSH UP TERHADAP AKURASI SMASH ATLET BOLA VOLI KLUB RIZSPORT DI KABUPATEN KUNINGAN - Asep Mulyana; Dani Nurdiansyah (STKIP Subang, 2025)
This study aims to determine the effect of push-up and clap push-up exercises on the smash accuracy of Rizsport Volleyball Club athletes in Kuningan Regency. The research method used was an experimental approach with a One Group Pretest-Posttest Design. The population consisted of 18 athletes, with 15 athletes selected as samples using purposive sampling, specifically those playing as spikers. The research instrument was a smash accuracy test conducted before (pretest) and after (posttest) the treatment. The treatment, consisting of push-up and clap push-up exercises, was carried out in 16 sessions over four weeks with a frequency of four training sessions per week. Data analysis using the paired sample t-test showed a significant difference between the pretest and posttest results, with a Sig. (2-tailed) value of 0.000 < 0.05. Therefore, it can be concluded that push-up and clap push-up exercises have a positive and significant effect on improving smash accuracy of Rizsport Volleyball Club athletes in Kuningan Regency.